On the political decision of audit market regulation: Empirical evidence of audit firm tenure and maximum durations within the European Union - Markus Widmann; Florian Follert; Matthias Wolz (Economies, 2021)
After almost every economic crisis and corporate scandal, political actors announce the need for stricter regulatory measures for financial markets and companies, in an attempt to appease their voters and defend their political agenda. Regarding the latest international financial crisis, the EU responded, among other things, with comprehensive regulation of the European audit market. In the context of auditor rotation, after 17 June 2016, the duration of audit engagements should not exceed a maximum of 10 years. In this paper, we therefore investigate whether there is empirical evidence behind the 10-year threshold-or is it simply arbitrary? Our aim is to evaluate the audit market reform by the European Union (EU) (Regulation (EU) No 537/2014 and Directive, 2014/56/EU) related to the objective of improving the quality of audits. Therefore, our article addresses the most crucial element of this reform, the implementation of a mandatory audit firm rotation for public interest entities (Regulation (EU) No 537/2014, Article 17). Based on a unique dataset of 11,834 firm observations from all listed companies within the EU between 2008 and 2017, we provide for the first time a discussion basis for the assessment of audit market interventions by the EU. Hence, we compare the new maximum durations with average audit tenure in the particular member states. Even where we present only descriptive results, our results at least indicate that the "magic number" 10 (years) could be more the result of a political process-i.e., a consent between the European institutions-rather than evidence based. Therefore, our findings shall serve as a first starting point in the discussion of a vast and interdisciplinary research field.
Keywords: 330; audit market; auditor tenure; decision-making; EU; Public Choice; regulation; rotation